A transect of environmental variability across South Asia and its influence on Late Pleistocene human innovation and occupation. (21st August 2017) - Roberts, Patrick; Blinkhorn, James; Petraglia, Michael D.
ABSTRACT: Climate change is frequently highlighted as a key driver of biological evolution and cultural innovation in our species. It is often seen as influencing behavioural plasticity and the development of buffering mechanisms, for example in the form of more efficient technology and subsistence strategies. However, such hypotheses are yet to be studied in detail in South Asia, despite improving Late Pleistocene palaeoenvironmental records in this region and its crucial position in human dispersals beyond Africa. Here, we review evidence for technological and behavioural innovation across three regions of South Asia: the Thar Desert (north‐west India), the Jurreru River Valley (south‐east India), and the lowland Wet Zone of Sri Lanka. Together these areas form an ecotone from hyper‐arid desert to humid rainforest that show different dynamics in the Late Pleistocene, and particularly during the Last Glacial Maximum. The archaeological records from each of these areas demonstrate a distinct nature and tempo of cultural change, probably reflecting, to some extent, the influence of climate change on forming heterogeneous local environments. Overall, however, the mosaic environments of South Asia made it an attractive region for the persistence of our species and their gradual uptake of cultural innovations during the Late Pleistocene.